THE INFLUENCE OF PERCEPTIONS OF LEADERSHIP STYLE AND ORGANIZATIONAL BEHAVIOR ON EMPLOYEE PERFORMANCE AT THE INVESTMENT OFFICE AND ONE-STOP INTEGRATED SERVICES OF LAMPUNG PROVINCE - Laila Rosita HN; Juhri Abdul Muin; Junaidi Junaidi (Saburai International Journal of Social Sciences and Development, 2023)
A good leader will definitely get good performance from his subordinates. Employee performance is a real behavior displayed by each employee as work achievements produced in accordance with his role in the organization. This study aims to examine the influence of variables partially or simultaneously the perception of leadership style and organizational behavior together on employee performance at the Investment Office and One-Stop Integrated Services of Lampung Province. The population in this study is employees in the Environment of the Investment Office and One-Stop Integrated Services of Lampung Province, totaling 85 people. Sample The research to be studied considering the number of the population is limited in determining this sample, the author uses the Slovin formula with a sampling error error rate of 10 percent so that the number of samples is 46 people. The results showed that the perception of leadership style partially affects the performance of employees of the Investment Office and One-Stop Integrated Services of Lampung Province. Organizational behavior variables affect employee performance in the Investment Office and One-Stop Integrated Services of Lampung Province and variables of Perception of leadership style and organizational behavior together have a positive and significant effect on the performance of employees of the Investment Office and One-Stop Integrated Services of Lampung Province.